Analisis Faktor Yang Mempengaruh Harga Saham Perusahaan Pertambangan Yang terdaftar Di Bursa Efek Indonesia Perusahaan Pertambangan Periode 2018-2022 - Yosa, Yosi Octaviani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
Mining companies are very important in economic growth in Indonesia. Share prices in the 2018-2022 period in mining companies experience fluctuations that can make investors confused and hesitant in investing in the capital market. Therefore, companies need to determine what factors are aspects in influencing a company's stock price.This research aims to determine the effect of inflation, exchange rates, gross domestic product on stock prices. The population in this research is all energy sector mining companies for the 2018-2022 period registered on the IDX. The sampling technique in this research uses the Purposive Sampling method, namely a sampling technique using several criteria so that the total sample is 42 companies. The analytical method used in this research is the SPSS 23 multiple linear regression method. The research results show that inflation has a significant effect on the share prices of mining companies listed on the Indonesia Stock Exchange for the 2018- 2022 period. The exchange rate has a significant effect on the share prices of mining companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Gross Domestic Product has a significant effect on the share prices of Mining Companies listed on the Indonesia Stock Exchange for the 2018-2022 period. And inflation, exchange rate, gross domestic product have a significant effect together (simultaneously) on share prices of mining companies listed on the Indonesia Stock Exchange for the 2018-2022 period.